Marketing Mix Dalam Pemasaran Digital Brand Hijab Rayyah Dan Peran Brand Hijab Rayyah Dalam Industri Kreatif Sub-Sektor Fashion - Yuliady , Fahmi; El Madja , Nur Mahmudah (Institut Pertanian Bogor, 2023)
Micro, Small and Medium Enterprises (MSMEs) are privately owned or group businesses. Marketing Mix in digital marketing is used by MSMEs so that their products can be recognized by the public both nationally and globally. In digital marketing, people can see products that are marketed digitally. MSMEs actors use the marketing mix to focus marketing efforts. MSMEs Brand Hijab Rayyah in Sidoarjo is an individual business that sells hijab products and has an important role in the creative industry of the fashion sub-sector in Indonesia. This study aims to analyze the marketing mix in digital marketing and the role of the Rayyah Hijab Brand in the Creative Industry, the Fashion Sub-Sector. This study uses a descriptive qualitative method with the marketing mix theory, according to Kolter and Armstrong. Product, price, place, and promotion will be analyzed. The role of the Rayyah Hijab Brand in the Creative Industry, Fashion Sub-Sector. The results of this study are that the Rayyah Hijab Brand implements digital marketing by utilizing Instagram to promote its sales. The strategy used by MSMEs owners is to provide a place for promotion by arranging attractive photos, holding giveaways, making discounts on each product on certain days and offering endorsements to celebgrams. The Hijab Rayyah brand implements 4P (product-price-place-promotion) in its digital marketing mix. The Rayyah Hijab Brand MSMEs also support the development of the Fashion Sub-Sector Creative Industry.